Pengaruh profitabilitas, likuiditas, solvabilitas, dan rasio nilai pasar terhadap return saham pada perusahaan pertambangan di BEI tahun 2016 - 2020 - Pradana, Julius Gaharu; Maryono, Maryono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Stock return is the amount of profit obtained by investors on the investment made. This study aims to examine the effect of Return On Assets, Current Ratio, Debt To Equity Ratio and Price Earning Ratio on stock returns in mining companies listed on the Indonesia Stock Exchange in 2016 - 2020. Determination of research samples using purposive sampling method is a sampling technique with certain criteria obtained as many as 195 sample companies. The research data analysis method used regression analysis with the SPSS version 26 application. The results showed that Return On Assets had a significant positive effect on stock returns, Current Ratio and Debt To Equity Ratio had no effect on stock returns, and Price Earning Ratio had a significant positive effect on stock returns.